Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense—21. Pentacomia paranigrimarginata sp. nov. and P. nigrimarginata Huber with revised key to Pentacomia species (Coleoptera: Cicindelidae) - Moravec, Jiří; Brzoska, David (Zootaxa, 2019)
A new species of the genus Pentacomia Bates, 1872 (restored to the original concept of the genus by Moravec 2018a) is described from Bolivia as P. paranigrimarginata sp. nov. The new species is compared to P. nigrimarginata Huber, 1999 of which the differential diagnosis and redescription are also given. Both species are illustrated with colour photographs of the habitus and diagnostic characters. A revised key to 12 recognized species of Pentacomia with illustrative figures of important diagnostic characters is given.